ANALISIS KESULITAN SISWA DALAM MEMAHAMI PERUBAHAN LINGKUNGAN PADA PEMBELAJARAN IPA SD - Adisty Yuliastri, Adisty; Amelia, Lisa; Vebrianto , Rian (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Science learning in elementary schools aims to help students understand natural phenomena and the relationship between humans and their environment. However, in the learning process there are still many students who experience difficulties, especially in understanding environmental changes and the impact of human activities. This study aims to analyze students' difficulties in understanding these concepts in science learning. The research used a descriptive method with a qualitative approach. Data were collected through observation, interviews, and concept understanding tests. The results of the study show that students experience several difficulties, including low conceptual understanding, difficulty connecting the material with real-life situations, limited use of learning media, and low scientific literacy skills. Therefore, teachers need to use more varied and contextual learning methods and media to help students better understand the material about environmental changes and the impacts of human activities.